Immediate and long term results of percutaneous coronary angioplasty in patients aged 70 and over. Issue 2 (February 1992) - de Jaegere, P; de Feyter, P; van Domburg, R; Suryapranata, H; van den Brand, M; Serruys, P W
Abstract : OBJECTIVE–To study the immediate and long term clinical success of percutaneous transluminal coronary balloon angioplasty in patients over 70 years old. DESIGN–Patients undergoing percutaneous transluminal angioplasty were prospectively entered in a specially designed database. The clinical and angiographic data of all patients over 70 were reviewed. Follow up data were collected by interview, during outpatient visits, by questionnaire, or through the referring physician. SETTING–A tertiary referral cardiac centre. PATIENTS–166 patients over 70 (median 73, range 70-84) underwent coronary angioplasty because of unstable angina (81 patients), stable angina (76 patients), or acute myocardial infarction (nine patients). RESULTS–The initial clinical success rate was 86% (142 of 166 patients). A major procedural complication occurred in 10 patients (6%): four patients (2%) died, six patients (4%) underwent emergency bypass surgery, and five patients (3%) sustained an acute myocardial infarction. In 14 patients (8%) coronary angioplasty did not significantly reduce the diameter stenosis but there were no associated complications. A total of 226 lesions were attempted. The initial angiographic success rate was 192 out of 226 lesions (85%). The median follow up was 21 (range 0.5-66) months. Sixteen patients (10%) died during follow up, eight patients (5%) sustained a non-fatal myocardial infarction, 21 patients (13%) underwent a second or third balloon dilatation, and 17 patients (10%) underwent elective bypass surgery. Of the 146 survivors, 99 patients (68%) had sustained clinical improvement. The estimated survival at four years (Kaplan-Meier method) was 89 (SD 4)%. The event free survival at four years for the total study population was 61 (8)%. Multivariate logistic regression analysis showed that the extent of vessel disease was the only independent predictive factor for event free survival: the event free survival rate was 81 (10)% at four years for patients with single vessel disease, compared with 45 (12)% for patients with multivessel disease. CONCLUSIONS–Coronary angioplasty in patients over 70 was a safe and effective treatment for obstructive coronary artery disease. The extent of vessel disease, and not the completeness of revascularisation, was the only independent predictive factor for event free survival.